LOYALITAS NASABAH DAN KINERJA PERBANKAN DI INDONESIA - Nurul Aisyah Rachmawati; Lindawati Gani; Hilda Rossieta (University of Merdeka Malang, 2017)
The purpose of this study was to investigate the impact of customer loyalty on firm performance in the banking industry in Indonesia. This study used a sample of banking firms listed on the Indonesian Stock Exchange. The data was processed and analyzed by Partial Least Square (PLS). We hypothesized that firm’s financial performance, market performance, and non-financial performance were positively affected by customer loyalty. The results provided evidence which was consistent with the hypothesis. It showed that customer loyalty provided incremental information to the firm’s performance that consisted of financial performance, market performance, and non-financial performance.